AFFORDANCES IN DIGITAL DETOX AND PRODUCTIVITY APPS - Karlsen, Faltin (AoIR Selected Papers of Internet Research, 2021)
The smartphone has become a crucial devise in everyday life, providing access to a range of communication, entertainment and utility tools. This has led to concern about intrusive media and worries that tech companies take advantage of our "easily distracted mind". This has also incited a booming app industry where digital detox and productivity apps are offered as tools to restrain smartphone use. The aim of this study is to add new empirical data and a conceptual framework to shed new light on this issue. The analysis is based on descriptions of 70 digital detox and productivity apps retried from the App Store and Google Play. The analysis focus on affordances, and distinguishes between two broad categories: undesign affordances, which comprise affordances that punish or inhibit certain types of use and gamification affordances which, in general, reward the user or encourage certain user behavior. The product description is also subject to a discourse analysis. A general finding is gamification affordances such as rewards, achievements, and ratings are generously used in most apps regardless of what kind of context it is meant to be used. More relentless undesign affordances, such as complete blocking of the smartphone is uses to a much lesser degree. The frequent use of gamification design means that the apps can, paradoxically, direct more attention toward the smartphone.